Silício na indução de resistência em plantas de trigo às formas alada e áptera de Sitobion avenae (Fabricius) (Hemiptera : Aphididae) - Dias, Polianna Alves Silva (2012)
Among the factors affecting wheat grain yield and quality, insects are notorious by the degrading effects, which can be reduced by silicon use. Despite the knowledge of silicon effects on the increase of antibiosis and non-preference of plants to apterous aphids, studies on the species Sitobion avenae (Fabricius) (Hemiptera: Aphididae) and the effect of silicon on the biology and preference for the host plant by alate aphids are scarce. This research determined the effect of silicon on the biology of alate and apterous forms of S. avenae; and the non-preference of alates for wheat plants with or without silicon fertilization. Antibiosis tests were conducted on wheat detached leaf over agar-water 1% solution in climatized chamber at 23 ºC. Non-preference tests were performed in climatized room at 23 ºC with alate aphids on vegetative and reproductive stage wheat plants. Silicon content in plants fertilized or not fertilized with silicon was analyzed. Silicon fertilization did not influence immature S. avenae mortality and development time. The greatest total fecundity was observed for apterous females on the control treatment. Silicon reduced fecundity, reproductive period and longevity of apterous females, but did not affect these biological traits of alate females. The greatest net reproductive rate (Ro) was observed for apterous on the control treatment, showing that silicon reduced fecundity of these insects. However, for alates, silicon did not affect this trait. The mean generation time (T), for both apterous and alate aphids reared on silicon treated plants, reduced. Silicon application did not affect the net rate of population increase (rm). The greatest values of the finite rate of original population increase (λ) were observed for apterous aphids, in both control and silicon fertilization. Non-preference testes of S. avenae for wheat, in vegetative and reproductive stages, showed that plants receiving silicon on its fertilization had lower number of insects than the control. Wheat plants subjected to silicon fertilization had silicon content two times greater on leaves and ears than control plants. The biology of apterous adults was negatively affected by silicon application, while the biology of alate forms was not. Silicon fertilization via soil induced resistance mechanism by non-preference on wheat plants to alate forms of S. avenae.